Relatedness and competence in college students' response to perceived facilitators and inhibitors of learning - Reyes, Melissa Lopez (Animo Repository, 2022)
In five focus group discussions in Philippine universities, undergraduate students described and evaluated the activities in their courses, their teachers and classmates as they contribute to their learning, and their own motivation, learning strategies, and valuing of education. It emerged that supportive peers and teachers, highly relevant lessons, engaging activities, and valuing of both familial and personal welfare were seen as facilitators of leaning by the students, while demoralizing classroom environments, the irrelevance of the subject matter, unreasonable requirements, and competing demands for student attention were perceived as inhibiting learning. The youth's accounts of their learning strategies, motivation, and valuing of education in the face of these facilitators and indicators of learning revealed their construals of relatedness, competence, and their emerging adult identity.